The Relationship of Diet and Excessive Cholesterol Levels on the Incident of Stroke In Batin Mangunang Hospital, Agung Kota - Fitri Anita; Adhi Nurhartanto; Anggie, Anggie Stiexs (Global Indonesia Health Care (GOICARE), 2024)
Dietary habit is something method in arrangement quantity and type food For maintain health , nutritional status , prevention or help recovery disease . People at risk experience enhancement cholesterol is those who have habit pattern eat foods rich in saturated fat . The prevalence of stroke in Indonesia is 10.9% or estimated as many as 2,120,362 people and prevalence happen stroke in Lampung Province as many as 16,233 people. Based on results A pre- survey conducted at Batin Mangunang Regional Hospital, Kota Agung, of 10 stroke patients , found 7 of them own pattern poor eating and levels​ cholesterol excessive . Research purposes This For know connection pattern eating and levels cholesterol excessive to incident stroke at Batin Mangunang Hospital , Agung City. Types of research This is quantitative with design study using cross sectional. Retrieval technique sample using purposive sampling. technique Data collection uses recorded data medical and FFQ questionnaires . Study This conducted in June 2023. Research sample totaling 31 respondents . Analysis bivariate in study This using the gamma test. Research results on variables pattern Eat with the incidence of stroke obtained p value 0.045<0.05 and for variable rate cholesterol excessive with The incidence of stroke obtained a p value of 0.037<0.05 so can concluded that there is significant relationship​ between pattern and rate cholesterol excessive to incident stroke disease . Recommended For always guard pattern Eat with consume containing foods​ carbohydrates , protein, vegetables and fruit as well as reduce foods high in fat.